A combination of dexmedetomidine and ketamine for a child with primary carnitine deficiency posted for cataract extraction. (April 2017) - Ganigara, Anuradha; Nishtala, Madhavi; Morubagal, Manasa; Ramavakoda, Chandrika Y.
Abstract: Primary carnitine deficiency (PCD) is an inherited disorder of fatty acid metabolism. Patients with PCD pose pertinent anaesthetic risk factors which need to be addressed before taking up for surgery under anaesthesia. Inappropriate selection of anaesthetic agents, coexisting myopathy and metabolic decompensation can lead to perioperative catastrophes in children with fatty acid oxidation defects. The indications for combination of dexmedetomidine and ketamine infusion are mostly limited to procedural sedation in perioperative anaesthesia care. We describe the case of a child with PCD and bilateral cataract who underwent phacoemulsification and intra ocular lens placement with dexmedetomidine and ketamine infusion for intraoperative maintenance of anaesthesia.